Tanggung Jawab Negara Dalam Pemenuhan Hak Hak Penganut Aliran Kepercayaan - Iftitah, Wulan Ramadhani; Nirahua, Salmon Eliazer Marthen; Nendissa, Renny Heronia (Jurnal Saniri, 2022)
Introduction: Constitutional Court Decision No. 97/PUU- XIV/2016 which gives recognition to adherents of a belief, with this decision the state guarantees the fulfillment of its constitutional rights but in its implementation there are still discriminatory actions against adherents of a belief. And it is clearly contrary to Article 29 (2) of the 1945 Constitution of the Republic of Indonesia.Purposes of the Research: The method used in this paper is met. The method used in this paper is the normative research method. The research method is normative.Methods of the Research: The method used in this paper is a normative research method. Results / Findings / Novelty of the Research: From this writing, it is found that the implementation of constitutional rights to adherents of a belief has not been carried out so well, which still requires regulation, attention, and legal certainty from the government as the executor of state responsibility.